Bruno's challenge : and other stories of the French countryside - Walker, Martin, 1947 January 23- (Alfred A. Knopf, 2022)
"Martin Walker presents his first collection of Bruno stories featuring all the familiar characters from the novels, the glories of the Périgord, and ample helpings of food and wine"--